Macroanatomical and subgross studies on the brachial plexus of the angora goat - Memduh Gezici (Eurasian Journal of Veterinary Sciences)
In this study, ihe formation and distribution of the brachial plexus were investigated in Angora goat, for this purpose, eight Angora goat in different ages and sex were used. It was observed that the brachial plexus in the Angora goat was formed by the ventral branches of the sixth, seventh, eighth cervical and lirst thoracic spinal nerves. It was seen that there wasn't a significant difference in the courses and distributions of the nerves arising from the brachial plexus in Angora goat in comparison with the other ones.